Lubok 8 - Ruckhäberle, Christoph; Siemon, Thomas (Leipzig : Lubok Verlag, 2009)
David Rayson, Roger Kelly, Claas Gutsche, Bob Matthews, Karl-Georg Hirsch, Serena Korda, Richard Woods, David Orme, Mark Titchner, Eileen Cooper, Julie Verhoeven, Adam Dant
Exemplar No.: 477/500
boek